2014
DOI: 10.1007/s00436-014-3763-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of the tegument protein RT10 from Raillietina tetragona

Abstract: Tegument antigens of tapeworm play an important role in modulation of host response and parasite survival. Characterizing appropriate antigens for parasite infection diagnosis and vaccination is rational and could have both economic and epidemiological significance in poultry industry. In the present study, a major protoscolex homologue (named RT10) of Echinococcus and Taenia spp. was amplified from Raillietina tetragona cestode. The RT10 cDNA was 1,877 bp long containing an open reading frame of 1,683 bp nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The activities of serum AST and ALT were not influenced by the diets, which reflected the fish livers were healthy compare to the FO group ( Chen and Li, 2014 ). The combined results of the hepatic sections stained by H&E and Oil red O showed that less lipid droplets in the liver of fish fed lysophospholipids above 0.05% compare to the fish fed FO diet.…”
Section: Discussionmentioning
confidence: 79%
“…The activities of serum AST and ALT were not influenced by the diets, which reflected the fish livers were healthy compare to the FO group ( Chen and Li, 2014 ). The combined results of the hepatic sections stained by H&E and Oil red O showed that less lipid droplets in the liver of fish fed lysophospholipids above 0.05% compare to the fish fed FO diet.…”
Section: Discussionmentioning
confidence: 79%